A study on Air Filled Porosity evolution in sludge composting. (1st January 2012) - Ruggieri, Luz; Gea, Teresa; Artola, Adriana; Sánchez, Antoni
Air Filled Porosity (AFP) is a key parameter in the composting process, conditioning oxygen availability and heat accumulation. Air pycnometry is considered the most adequate methodology for AFP determination. This technique requires withdrawing a sample of material from the composting mass for AFP measurement, which may alter its physical characteristics. A novel strategy that permits to measure AFP in situ during the composting process is presented in this study. Raw and Anaerobically Digested Sludges (ADS) have been used as substrates. A common trend in AFP evolution during the composting process has been observed in most of the cases.